Coastal aquaculture regulates phosphorus cycling in estuarine wetlands: Mobilization, kinetic resupply, and source-sink process. (1st May 2023) - Xiao, Kai; Pan, Feng; Li, Yurui; Li, Zhenyang; Li, Hailong; Guo, Zhanrong; Wang, Xinhong; Zheng, Chunmiao
Highlights: P fractions, geochemical behavior, and source-sink patterns were investigated in a shrimp pond enclosed by mangroves. Depth profiles of P, Fe, Mn, and as were obtained using an in-situ high-resolution dialysis device. P kinetic resupply was first evaluated via the DIFS model using TDP rather than DRP. Mangrove and pond sediments were important sources of DOP and DRP, respectively, for overlying water. Fe(III) and sulfate reduction co-regulated p remobilization in pond sediments. Abstract: Estuarine mangrove wetlands have gradually declined owing to the growing construction of aquaculture ponds. How the speciation, transition, and migration of phosphorus (P) adaptively change in the sediments of this pond-wetland ecosystem remains unclear. In this study, we used high-resolution devices to explore the contrasting P behaviors associated with the redox cycles of Fe-Mn-S-As in estuarine and pond sediments. The results showed that the construction of aquaculture ponds increased the content or percentage of the silt, organic carbon, and P fractions in sediments. Dissolved organic P (DOP) concentrations in pore water were fluctuant with depths, accounting for only 18±15% and 20±11% of total dissolved P (TDP) in estuarine and pond sediment, respectively. Furthermore, DOP was less strongly correlated with other P species, including Fe, Mn, and sulfide. The coupling of dissolved reactive P (DRP) and TDP with Fe and sulfide confirmed that P mobility is regulated by Fe redox cycling in estuarine sediments, whereas Fe(III) reduction and sulfate reduction co-regulate P remobilization in pond sediments. The apparent diffusion flux revealed all sediments acting as sources for TDP (0.04–0.1 mg m −2 d −1 ) to the overlying water, while mangrove sediments were sources of DOP, and pond sediments were major sources of DRP. The DIFS model overestimated the P kinetic resupply ability, which was evaluated using DRP rather than TDP. This study improves our understanding of P cycling and budget in aquaculture pond-mangrove ecosystems and has important implications for understanding water eutrophication more effectively. Graphical abstract: Image, graphical abstract